Hypotensive action of an aqueous extract of Pimenta dioica (Myrtaceae) in rats - Suárez, Adriana (2000)
The intra-venous (i.v.) hypotensive action of the final aqueous fraction of Pimenta dioica was studied in Spontaneously Hypertensive Rats (SHR). The rats were anaesthetized (sodium pentobarbital 50 mg/kg), the trachea, right carotid artery and jugular vein were cannulated for adequate ventilation, direct blood pressure measurement and intra-venous adrninistration of extracts, solutions and drugs. The arterial line was connected to a pressure transducer (Viggo-Spectramed model P23 XL) and a polygraph (Grass model 7H) and monitored continuously during the first five minutes afier plant extract adrninistration and then at 5 JlBd 15 minute intervals for one hour. Responses were taken as the maximum pressure changes observed during this periodo Increasing doses of the final aqueous fraction were given Lv. to groups of six SHR each. It produced a dose dependent decrease in blood pressure and the EDso was 45 mg/kg. To discard that the hypotensive effect of the extracts was due to its ionic composition, a solution containing KCI, NaCI, CaC12 and MgCl2 equivalent to the ion contents present in a dose of 50 mg/kg of total aqueous extract was injected to Sprague-Dawley rats (SDN) using the same method as described aboye. It did not produce significant changes in blood pressure. Pharmacological antagonistic studies were done injecting either autonomic ganglion, IX adrenoceptor,